Artistic Research Now: Status Quo Based on the Research and Innovation Initiatives of FilmEU_RIT and Beyond (International Journal on Stereo & Immersive Media, 2025)
Editorials typically start with discussions on emerging debates that may later establish new fields, often including future predictions and outlining potential roadmaps. Qua Vadis is a genre in its own right, as a result. This does not appear to be necessary or appropriate any longer when discussing artistic or practice-based research (from hereafter “artistic research”). Firstly, several opinions have already mapped out the potential future trajectories of artistic research. More importantly, a decade or more has usually passed since their original publication. Fifteen years have passed since an important issue of Art and Research: A Journal of Ideas, Contexts and Methods (Birell, ed. 2009: 1–2), which explored the emergent field from a myriad of angles, and just short of fifteen years ago, a seminal collection – The Routledge Companion to Research in the Arts (Biggs and Karlsson, eds. 2010: xiii–xvi) – was published that aimed to start the discussion from first principles.